Comunicación interna de los colaboradores del Gobierno Autónomo Descentralizado del cantón Vinces - Vera España, Lady Aura (2019)
Internal communication is a fundamental element for the company to efficiently execute its activities and achieve its planned objectives , so it is essential to be aware of all the inconveniences that intervene negatively in the functions performed daily by the GAD of the Canton Vinces , the labor disputes often occur in the organization for various reasons especially personal differences or because certain employees believe their ideas are better than their peers can also mention the organizational climate tense results in inefficient communication lack of leadership and teamwork are problems that also affects internal communication the motivation is another factor that affects internal communication in this organization , since the employees of the institution carry out activities assigned by their directors on many occasions in an excessive way The objective of the case presented is focused on knowing the communication process that It is usually carried out in the company, however some complications arise since many workers do not efficiently practice this great resource that is very important for any company to function properly